Análises morfológicas e bioacústicas em populações de Scinax hayii (Barbour, 1909) (Anura, Hylidae) ao longo da Mata Atlântica - Santos, Lucas Rodrigo dos [UNESP] (2015)
This study aims were to describe the morphometric, morphological and bioacoustic of Scinax hayii characters from the type locality and from three Operational Taxonomic Units to compare the localities with each other and registering founds variations at the characters analyzed. Were measured 18 morphometric characters in collected specimens on field and specimens provided of scientific collections. Morphological analysis was performed by the characters qualitative comparison and checking for the stripes and spots presence on the dorsal aspect. The bioacoustics analysis was performed with obtained recordings of recorded specimens in natural field conditions at all OTUs. Scinax hayii from Petrópolis has similar morphometric characters to OTU Serra do Mar. Specimens of OTU Planície Litorânea and Serra da Mantiqueira have smaller size (CRC: 34,2 - 41,5 mm; 31,5 - 42,2 mm; respectively). Scinax hayii from Petrópolis, Serra do Mar and Planície Litorânea are devoided stripes and spots on dorsal pattern. OTU Serra da Mantiqueira specimens differ from other locations by present dorsal coloration having stripes and spots. The S. hayii from Petrópolis vocalizations are shown like the OTU Serra do Mar call specimens. The recorded specimens vocalizations at OTUs Planície Litorânea and Serra da Mantiqueira differ from another locations and each other. Petrópolis and OTU Serra do Mar specimens by having similar morphological and bioacoustics characters indicate to be of the same species. The registered specimens at UTO Planície Litorânea have different morphological and bioacoustics characters from another locations, indicating that is a new specie. The UTO Serra da Mantiqueira specimens by having different morphological and bioacoustics characters from other locations indicate to be a new specie or the currently revalued specie as S. dolloi. In view of the morphological and bioacoustics analysis...